Autosolitons in trapped Bose-Einstein condensates with two- and three-body inelastic processes - Filho, V. S. [UNESP]; Abdullaev, F. Kh [UNESP]; Gammal, A. [UNESP]; Tomio, L. [UNESP] (American Physical Society (APS), 2001)
The conditions for the existence of autosolitons were considered in trapped Bose-Einstein condensates with attractive atomic interactions. The expression for the parameters of the autosoliton was derived using the time-dependent variational approach for the nonconservative 3-dimensional Gross-pitaevskii equation and their stability was checked. The results were in agreement with the exact numerical calculations. It was shown that the transition from unstable to stable point solely depends on the magnitude of the parameters.
Keywords: Algorithms; Computer simulation; Condensate treatment; Damping; Elasticity; Fiber optics; Phase transitions; Stabilization; Variational techniques; Autosolitons; Solitons